Evaluation of surgical outcomes in elderly patients with rib fractures: A single-centre propensity score matching study - Zhang, Dong; Jiao, Chenbo; Xi, Siqi; Wang, Langran; Li, Run; Zhang, Qiang (Frontiers in Surgery, 2023)
Background: Rib fractures are the most common injuries in chest trauma. Compared with younger patients, elderly patients with rib fracture have a higher incidence of complications and mortality. A retrospective study was conducted to investigate the effect of internal fixation compared with conservative treatment on the outcome of rib fracture in elderly patients. Material and methods: We used a 1:1 propensity score matching method to perform a retrospective analysis of 703 elderly patients with rib fractures treated in the Thoracic Surgery Department of Beijing Jishuitan Hospital between 2013 and 2020. After matching, the length of hospital stay, death, symptom relief and rib fracture healing were compared between the surgery and the control group. Results: The study included 121 patients receiving SSRF in the surgery group and 121 patients receiving conservative treatment in the control group. The length of hospital stay in the surgery group was significantly longer than that in the conservative group (11.39d vs 9.48d, p=0.000). After 9 months of follow-up, the fracture healing rate in the surgery group was significantly higher than that in the control group (96.67% vs 88.89%, p=0.020). The fracture healing time (p=0.000), improvement in pain score (p=0.000) and duration of pain medication use(p=0.000) were also significantly better in the surgery group than in the control group. Conclusion: Compared with conservative treatment, surgical treatment can prolong hospital stay to some extent. However, it has the advantages of more rapid healing and lessened pain. For rib fractures in elderly individuals, surgical treatment is a safe and effective option under strict surgical indications and is recommended.